An experimental method for determination of poissons ratio in soils. - Espol (1969)
The theory of elasticity furnishes equations that tie together the stresses and displacernents induced in an elastic body by the action of exterior causes. its target is to determine the intensity and orientation of these stresses and displacernents at any point. when a cylindrical elastic body is subjected to axial tension or compressions along the longitudinal axis, without lateral constraint, the elastic solution yields: aawz = e: = i a + jj 2μ 2 + 3>-μ f where: w = vertical displacement e:q, = strain per unit of height a and jj = lame's elastic constants. a and μ are the only two independent constants that appear relating the stresses and strains in the general elastic equations. μ is also called the shear modulus. it relates the shear stress to the shear strain through the expression: t = μy where: t = shear stress y= shear strain f = unit compressive or tensile force.